IMPLEMENTASI PROGRAM TADARUS KELAS V DI SDN TEMBONG 2 - Azye Albar Bachtiar; M Taufik; Istinganatul Ngiwiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the Al-Qur’an tadarus program for fifth-grade students at SDN Tembong 2. The tadarus program is one of the religious activities carried out regularly as part of fostering religious habits in the elementary school environment. This study uses a qualitative approach with a descriptive method. Data collection techniques were conducted through observation, interviews, and documentation with fifth-grade teachers as well as several students involved in tadarus activities. The results of the study indicate that the implementation of the tadarus program is conducted every morning before teaching and learning activities begin, with a duration of approximately 15–20 minutes. Teachers act as guides and supervisors of the activities, while students take turns reading the Al-Qur’an in small groups. This program received positive responses from students and teachers and was considered capable of improving the ability to read the Qur’an, strengthening religious character, and creating a conducive classroom atmosphere full of spiritual values. However, some challenges faced in the implementation of the program include differences in students' Qur’an reading abilities and time constraints. Nevertheless, improvement efforts continue through intensive guidance and grouping students based on their abilities. Thus, the tadarus program at SDN Tembong 2 has been proven to have a positive impact on the formation of students' character and religious habits, and it is worthy of further development and serving as a model of good practice for other elementary schools.